Comparison between 3D volumetric rendering and multiplanar slices on the reliability of linear measurements on CBCT images: an in vitro study - Thais Maria Freire FERNANDES; Julie ADAMCZYK; Marcelo Lupion POLETI; José Fernando Castanha HENRIQUES; Bernard FRIEDLAND; Daniela Gamba GARIB (University of São Paulo, 2015)
OBJECTIVE: The purpose of this study was to determine the accuracy and reliability of two methods of measurements of linear distances (multiplanar 2D and tridimensional reconstruction 3D) obtained from cone-beam computed tomography (CBCT) with different voxel sizes. MATERIAL AND METHODS: Ten dry human mandibles were scanned at voxel sizes of 0.2 and 0.4 mm. Craniometric anatomical landmarks were identified twice by two independent operators on the multiplanar reconstructed and on volume rendering images that were generated by the software Dolphin®. Subsequently, physical measurements were performed using a digital caliper. Analysis of variance (ANOVA), intraclass correlation coefficient (ICC) and Bland-Altman were used for evaluating accuracy and reliability (p<0.05). RESULTS: Excellent intraobserver reliability and good to high precision interobserver reliability values were found for linear measurements from CBCT 3D and multiplanar images. Measurements performed on multiplanar reconstructed images were more accurate than measurements in volume rendering compared with the gold standard. No statistically significant difference was found between voxel protocols, independently of the measurement method. CONCLUSIONS: Linear measurements on multiplanar images of 0.2 and 0.4 voxel are reliable and accurate when compared with direct caliper measurements. Caution should be taken in the volume rendering measurements, because the measurements were reliable, but not accurate for all variables. An increased voxel resolution did not result in greater accuracy of mandible measurements and would potentially provide increased patient radiation exposure.